1993
DOI: 10.1152/jappl.1993.74.3.1061
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived relaxing factor activity in rat lung during hypoxic pulmonary vascular remodeling

Abstract: We have investigated the role of endothelium-derived relaxing factor in modulating hypoxic pulmonary vasoconstriction by inhibiting its synthesis with the false substrate NG-monomethyl-L-arginine (L-NMMA) in the isolated blood-perfused lungs of Wistar rats after chronic hypoxia (CH, fractional inspiratory O2 concentration 10%) for 15 h, 2 days, and 7 days. Lungs were perfused with blood of normal hematocrit at constant flow (18 ml/min) ventilated with 1) 95% air-5% CO2 (normoxia) and 2) 2% O2-5% CO2-93% N2 (hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
2
23
1
Order By: Relevance
“…Pharmacological or genetic inhibition of NO synthase, particularly the endothelial isoform, increases hypoxic pulmonary vasoconstriction in rodents. 17,18 Both inhaling NO 19 and inhibition of cGMP hydrolysis using the phosphodiesterase type 5 inhibitor, sildenafil, 20 reduce acute hypoxia-induced pulmonary hypertension and chronic sildenafil use reduces established pulmonary hypertension in resident highlanders. 21 The most common isoform of sGC is active as a heterodimer, composed of an α1 subunit and a heme-containing β1 subunit, and expressed in the smooth muscle layer of the pulmonary vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological or genetic inhibition of NO synthase, particularly the endothelial isoform, increases hypoxic pulmonary vasoconstriction in rodents. 17,18 Both inhaling NO 19 and inhibition of cGMP hydrolysis using the phosphodiesterase type 5 inhibitor, sildenafil, 20 reduce acute hypoxia-induced pulmonary hypertension and chronic sildenafil use reduces established pulmonary hypertension in resident highlanders. 21 The most common isoform of sGC is active as a heterodimer, composed of an α1 subunit and a heme-containing β1 subunit, and expressed in the smooth muscle layer of the pulmonary vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…48 -54 Whereas several investigators have found a reduced HPV response after long-term exposure to hypoxia, 48 -54 other groups have reported an enhanced response or no change in HPV after exposure to a low O 2 tension. 48,49 In addition to these 2 factors (animal species and length of hypoxic exposure), we showed that the effect of chronic hypoxia on acute hypoxia-induced responses depended on the localization of the PASMCs within the media. These results emphasize regional differences in PASMC populations within the media.…”
Section: Effects Of Chronic Hypoxia On Pasmc Morphology and Responsesmentioning
confidence: 88%
“…Moreover, while some groups have evidence for impaired nitric oxide pro-30 mmHg) was two-fold greater in the WKY lung compared with the F344 lung (Figure 2), with no duction in the lungs of rats [26 ] kept in a chronic hypoxic environment, we and others have found that overlap in the response between the two strains. Chronic exposure of both rat strains to 10%O 2 in a normobaric synthesis is preserved or possible increased [23,24].…”
Section: Abstract Hypoxia Vasoactive Factors Genetics Rat Strainsmentioning
confidence: 94%
“…In the of this amino acid have been used by several groups to explore the role of nitric oxide in HPV [22][23][24]. There search for humoral mediators many vasoactive substances have been considered as candidates.…”
Section: Abstract Hypoxia Vasoactive Factors Genetics Rat Strainsmentioning
confidence: 99%